A Practical Guide to Atmospheric Simulation Chambers - Doussin, Jean-François; Fuchs, Hendrik; Kiendler-Scharr, Astrid; Seakins, Paul; Wenger, John (Springer International Publishing : Imprint: Springer, 2023)
This open access title presents atmospheric simulation chambers as effective tools for atmospheric chemistry research. State-of-the-art simulation chambers provide unprecedented opportunities for atmospheric scientists to perform experiments that address the most important questions in air quality and climate research. The book covers technical details about chamber preparation and practical guidelines on their usage, while also delivering relevant historical and contextual information. It not only serves as a key publication for knowledge transfer within the simulation chamber research community, but it also provides the global atmospheric science community with a unique resource that outlines best practice for the operation of simulation chambers. The authors summarize the latest advances in chamber interoperability and standard protocols in order to provide the research community and the next generations of scientists with a unique technical reference guide for the use of simulation chambers. The volume will be of great interest to researchers and graduates working in the fields of Atmospheric and Environmental Sciences.